2002
DOI: 10.1037/0090-5550.47.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based diabetes self-management and support: Initial outcomes from the Diabetes Network project.

Abstract: The Diabetes Network (D-Net), a randomized trial of an Internet-based, diabetes self-management and peer support intervention, was evaluated after 3 months. Design: The study assessed separate and combined effects of diabetes self-management and peer support. Outcomes included physiologic, behavioral, mental health, and website usage. Results are presented on the first 160 type 2 diabetes patients recruited from 16 primary care offices. Of those eligible, 61% participated in the study. Results: There was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
195
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(195 citation statements)
references
References 40 publications
0
195
0
Order By: Relevance
“…Based on consultation with two experts in behaviour change interventions (SM) and eHealth (JP), two pre-defined sets of papers were sampled from two published systematic reviews. 66,67 Twenty-five papers published between 2001 and 2005 were included, reporting interventions for: physical activity [68][69][70][71][72] ; dietary behaviour [73][74][75][76][77][78][79][80][81][82] ; and physical activity and dietary behaviour. [83][84][85][86][87][88][89][90][91][92] Fourteen papers reported Internet and email-based interventions, [68][69][70][71]75,79,[81][82][83][84][85][86][87][88]90,92 three of which contained telemedicine components [84][85][86] ; seven papers reported computer-based interventions 73,…”
Section: Phase 1 Diversity Samplingmentioning
confidence: 99%
“…Based on consultation with two experts in behaviour change interventions (SM) and eHealth (JP), two pre-defined sets of papers were sampled from two published systematic reviews. 66,67 Twenty-five papers published between 2001 and 2005 were included, reporting interventions for: physical activity [68][69][70][71][72] ; dietary behaviour [73][74][75][76][77][78][79][80][81][82] ; and physical activity and dietary behaviour. [83][84][85][86][87][88][89][90][91][92] Fourteen papers reported Internet and email-based interventions, [68][69][70][71]75,79,[81][82][83][84][85][86][87][88]90,92 three of which contained telemedicine components [84][85][86] ; seven papers reported computer-based interventions 73,…”
Section: Phase 1 Diversity Samplingmentioning
confidence: 99%
“…Of the four studies conducted for over one year [15,20,23,24], only Cleland [20] found significant long-term effects of the intervention. The others, all conducted with obesity patients, found no long-term effects of the interventions.…”
Section: Effectiveness Over Timementioning
confidence: 99%
“…Four studies [29,30,20,31] compared Internet-mediated interventions to usual care, while McKay [23] compared monitoring to other interventions. Because the same physiological outcomes (blood glucose levels) were measured across these studies, we were able to directly compare specific test results (see Table 6) and found that the interventions generally showed positive impacts on health outcomes.…”
Section: Diabetesmentioning
confidence: 99%
See 2 more Smart Citations